From the Ghetto to the world: Batida, the Nexus Príncipe Discos-Filho Único and the legitimization of afrodiasporic music practices from the outskirts of Lisbon - Belchior, P.; Raposo, O. (Independence in 21st-century popular music: Cases from beyond Anglo-America, 2025)
In this chapter we address the emergence of batida in the local context of Lisbon’s peripheral Afro-Portuguese neighborhoods. We focus on the joint role of two independent music production organizations, the record label Príncipe Discos and the related cultural association Filho Único, in legitimating and disseminating batida outside of peripheral Lisbon neighborhoods and within the international subfield of electronic dance music (EDM). After accounting for the emergence of batida, we reflect on the active and transformative role of these independent cultural mediators between batida DJs and a consuming audience. Three elements are of special interest: (1) the emergence of batida in the Portuguese Afrodiasporic soundscape, (2) the conditions that enabled it to reach outside the original context of peripheral neighborhoods, and (3) the politics developed by Príncipe in collaboration with Filho Único to disseminate the work of the DJs involved in batida. Later in the chapter we discuss the role of Príncipe and Filho Único in a critical dialogue with notions of cultural intermediation (Bourdieu 1984) and of the independents as the new cultural entrepreneurs (Leadbeater and Oakley 1999). We approach this relationship based on data collected through semi-directed interviews with staff members at Príncipe and Filho Único and with the DJs published by Príncipe. We also carried out an analysis of the discourse about batida in the specialized music press, on the label’s website and on digital platforms such as Bandcamp.